2005
DOI: 10.1158/0008-5472.can-04-3701
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib Abolishes Tumor Necrosis Factor–Related Apoptosis-Inducing Ligand Resistance via a p21-Dependent Mechanism in Human Bladder and Prostate Cancer Cells

Abstract: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is a member of the tumor necrosis factor family of cytokines that induces apoptosis in some tumor cells but not in normal cells. Unfortunately, many human cancer cell lines are refractory to TRAIL-induced cell death, and the molecular mechanisms underlying resistance are unclear. Here we report that TRAIL resistance was reversed in human bladder and prostate cancer cell lines by the proteasome inhibitor bortezomib (PS-341, Velcade). Synergistic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
92
3
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(100 citation statements)
references
References 49 publications
4
92
3
1
Order By: Relevance
“…Although some potential mediators of this sensitization effect have been indicated, for example p21 (Lashinger et al, 2005), c-FLIP (Sayers et al, 2003), Bik and Bim (Nikrad et al, 2005), whereas others have been excluded, for instance Bcl-2 (Nencioni et al, 2005), Bax (He et al, 2004) and Bcl-xL (Johnson et al, 2003), the specific contribution of NF-kB to this phenomenon remained unclear. In fact, there is only one other report pointing to a differential role of proteasome versus NF-kB inhibition in the regulation of TRAIL-induced apoptosis in glioblastoma cells, possibly by blocking degradation of active caspases (Kim et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Although some potential mediators of this sensitization effect have been indicated, for example p21 (Lashinger et al, 2005), c-FLIP (Sayers et al, 2003), Bik and Bim (Nikrad et al, 2005), whereas others have been excluded, for instance Bcl-2 (Nencioni et al, 2005), Bax (He et al, 2004) and Bcl-xL (Johnson et al, 2003), the specific contribution of NF-kB to this phenomenon remained unclear. In fact, there is only one other report pointing to a differential role of proteasome versus NF-kB inhibition in the regulation of TRAIL-induced apoptosis in glioblastoma cells, possibly by blocking degradation of active caspases (Kim et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Bortezomib, in combination with tumor necrosis factor-␣ (TNF-␣) or TNF-related-apoptosis-inducing ligand shows synergistic effect to induce apoptosis in human prostate and bladder cancer cells. 8,9 Enhanced radiation sensitivity with proteasome inhibition via downregulation of NF-B was first reported by Russo et al 27 in colorectal cancer cells. Pervan et al 28 demonstrated increased radiosensitivity by proteasome inhibition in the TRAMP-C1 prostate cancer tumor model.…”
Section: Commentmentioning
confidence: 95%
“…In preclinical studies, it has been reported that bortezomib (previously known as PS-341), which is a strong proteasome inhibitor, induces apoptosis in many solid tumors including prostate cancer cell lines. [8][9][10][11]17,18 Therefore, inhibition of proteasome activity could be a new strategy for the treatment of prostate cancer. In our study, we investigated the effects of bortezomib alone or in combination with radiation on androgen-independent DU145 human prostate cancer cells.…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations